Diurnal changes of CO2 net assimilation rate and related parameters in Pistacia vera L. - Novello V. (X GREMPA Seminar, 1998)
In Pistacia vera L., the average diurnal patterns of net CO2 assimilation, stomatal conductance and transpiration rates were assessed at the leaf surface during a clear summer day, with reference to the diurnal fluctuations of leaf temperature and photosynthetic photon flux. The rate of leaf gas exchange was highest at 9:00. The subsequent decline in net carbon assimilation did not appear to be related to changes in stomatal conductance (gs). The latter seemed to be primarily limited by vapour pressure deficit (VPD) of 3.8 kPa and leaf temperature (Tl) of 36 degrees C. Further, stomatal conductance declined at 13:00, at a time when VPD slightly increased to 4.2 kPa and Tl reached 38 degrees C. The partial gs recovery, two hours later, did not seem to be related to changes in the ambient conditions. The midday transpiration rate did not show any significant decline, hence leaf temperature did not change markedly. The photosynthetic efficiency declined at leaf temperatures higher than 31 degrees C.
10. GREMPA Seminar, 1996/10/14-17, Meknès (Morocco)